The Impact of Perioperative Blood Transfusion on Flap Survival: A Single-Center Review of Limb Salvage in the Trauma Setting - O'Brien, Devon; Pekcan, Asli; Stanton, Eloise; Roohani, Idean; Zachary, Paige; Parikh, Neil; Daar, David A.; Carey, Joseph N. (Journal of Reconstructive Microsurgery, 2024)
Limb salvage following traumatic lower extremity (LE) injury often necessitates blood transfusion for adequate tissue perfusion. Appropriate transfusion decision-making via a risk–benefit analysis could maximize the opportunity for flap survival. This study aims to examine the impact of perioperative blood transfusion on postoperative complications in traumatic LE reconstruction.A retrospective review was conducted at a level 1 trauma center on patients who underwent LE reconstruction between January 2007 and October 2023. Patient demographics, comorbidities, perioperative blood transfusions, flap characteristics, and postoperative complications were recorded. Outcomes investigated included postoperative amputation rates, infection, partial flap necrosis, and flap loss. Univariate analysis and multivariable logistic regression were performed to examine the impact of patient factors on flap necrosis.In total, 234 flaps met inclusion criteria. Of these, 149 cases (63.7%) received no transfusion during their hospital stay (Tf − ) and 85 cases (36.3%) received at least one unit of packed red blood cells intraoperatively through 48 hours following flap placement (Tf + ). Overall flap survival rates were similar across both cohorts (Tf + : 92.9 vs. Tf − : 96.6%, p = 0.198). The Tf+ cohort had significantly higher rates of partial flap necrosis (12.9 vs. 2.0.%, p < 0.001), amputation (6.0 vs. 0.7%, p = 0.015), and postoperative hardware infection (10.6 vs. 2.7%, p = 0.011) relative to the Tf− cohort. Multivariable logistic regression demonstrated that transfusion status was independently associated with a 5.1 fold increased risk of flap necrosis (p = 0.033).Transfusions administered intraoperatively through the acute postoperative period were associated with a significantly increased likelihood of flap necrosis. Surgeons should consider a conservative transfusion protocol to optimize flap viability in patients with traumatic LE injuries.
Keywords: transfusion; lower extremity; free flap; amputation; limb salvage; reconstruction